The Iconographic Program of the Vaulting System of the Nave Spire from the Church of the True Cross from Pătrăuți - Dragnev, Emile (Eikón / Imago, 2015)
This paper is dedicated to the iconographic program of the vaulting system of the nave spire from the church dedicated to the Elevation of the Holy Cross from Pătrăuți, in the context of the Palaeologue art and that of the Post-Byzantine painting. The author highlights the peculiarities of this program: the specific setting of the image of the Pantokrator inside the vault; the way of representing the angels’ registers; the content of the prophets’ register and the inscriptions on their rotuli; introducing the apostles’ register within the program of the tambour of the vault; the correspondence between the images situated in the back side of the oblique arches and the scenes from the lunettes. The author attempts to determine the sources of the prophetical inscriptions and their common message. The research hereby enables to estimate the place of the paintings from the vaulting system of the nave, holding an intermediate position between the traditions of the Palaeologue painting and that of the Post-Byzantine one, as well as their significance for the further evolutions of mural painting from Moldova.